Comparison of Vaginal Trinitroglycerin (TNG) and Vaginal Misoprostol in Cervical Ripening at term pregnancy - Batoul Teimouri; Marzieh Ghasemi; Nahid Sakhavar; Sima Khajeh Noori (Mashhad University of Medical Sciences, 2018)
Introduction: Cervical ripening is essential in vaginal delivery; so, a safe and suitable method should be considered for cervical ripening. Nowadays, different methods are used for cervical ripening, including estrogen gels, prostaglandins and TNGs that their preference is unclear. This study was performed with aim to compare vaginal misoprostol and trinitroglycerin (TNG) on cervical ripening at term pregnancy. Methods: This randomized clinical trial was performed in 2011 on 148 primigravida patients with term pregnancy and unfavorable cervix (Bishop score ≤ 4) who were candidate for induced vaginal delivery and referred to Zahedan Ali Ebne Abi Talib hospital. The patients were divided into two groups: group A (400 µg vaginal TNG) and group B (25 µg vaginal misoprostol). The outcomes in two groups were recorded in the forms by observation. Data was analyzed by SPSS software (version 11.5) and Chi-square and T-test. P<0.05 was considered significant. Results: After administration of the drugs, cervical ripening (P<0.001) and Bishop score (P<0.001) were significantly higher in vaginal misoprostol group than TNG group. Also, time duration from drug administration to delivery was significantly shorter in vaginal misoprostol group than TNG group (P<0.001). 1 and 5 minutes Apgar Scores were similar in two groups. The side-effects of drugs before delivery in misoprostol group were 11 cases (14.9%) and in TNG group were 29 cases (39.2%); two groups were significantly different in terms of the incidence of these side-effects (P<0.001). Conclusion: Misoprostol compared to TNG causes more effective and rapid cervical ripening and also has less side-effect.